REQUIREMENTS FOR DETERMINING THE LEVEL OF MATERIALITY IN THE AUDIT - Tolqinov Dilshodkhoja Olim Ogli (International Journal of Innovations in Engineering Research and Technology, 2021)
This article addresses the requirements for determining the level of materiality in an audit. As a result of the research, the determination of the level of materiality in the audit has been scientifically substantiated.